Bacterial Vaginosis in Well-Educated Married Women with Risk Factor for Vulvovaginal Flora Disruption - Nurinnisa, Zarifa; Andarini, Sri; Hevy Purwaningtyas, Nuretha (Jurnal Ilmu Kedokteran Keluarga, 2023)
Bacterial vaginosis is a reproductive system infection that causes a variety of symptoms. This condition can be caused by a variety of risk factors, including Vulvovaginal Flora Disruption. This case was detected in a Malang City primary health care. An in-depth history is collected to identify risk factors, followed by a home visit to detect risk factors. We shall explore the role and use of family medicine in cases of bacterial vaginosis in this case report. Because of the complicated interplay of biopsychosocial variables, comprehensive and holistic treatment is required.